Professor Zbigniew Moser - Biography & Bibliography - Zakulski, Wojciech (Journal of Mining and Metallurgy, Section B: Metallurgy, 2012)
On 13 April, 2011, Professor Zbigniew MOSER passed away. He was a Member of Editorial Board of the Journal of Mining and Metallurgy, Section B – Metallurgy, as well as the Chairman of the Associated Phase Diagram and Thermodynamics Committee (Poland, Bosnia&Herzegovina, Bulgaria, Croatia, Czech Republic, Hungary, Montenegro, Romania Serbia, Slovakia, and Slovenia).